Penyuluhan Hukum Tentang Penanggulangan Tindak Pidana Narkotika Di Desa Kertaungaran, Kuningan - Akhmaddhian, Suwari; Yuhandra, Erga; Budiman, Haris (Empowerment, 2022)
Every citizen has the right in law and justice, because of that the government made Law number 16 of 2011 concerning Legal Aid to protect its citizens in the event of a disaster that befalls the community. The purpose of community service is more focused on the people or villagers, while the other objectives of this counseling are the parents who can add information related to the process of handling criminal acts and how to follow up in the event of a crime. The method used is by way of lectures and discussions then ends with questions and answers. The results obtained from this community service are that the community is more sensitive and knows how criminal law and the process of resolving criminal acts, starting from the investigation and investigation, prosecution and court decision. defendant.